A new genus and three new species of Phyllocoptinae (Acari: Eriophyidae) from South China - Li, De-Wei; Wang, Guo-Quan; Wei, Sui-Gai (Zootaxa, 2007)
In this paper, a new genus and three new species of eriophyid mites from Heng County and Longlin County, Guangxi Zhuang Autonomous Region, South China are described and illustrated: Calpentaconvexus eyrei n. gen. and n. sp. infesting Castanopsis eyrei (Champ. ex Benth.) Tutch. (Fagaceae); Phyllocoptruta subcoriaceae n. sp. infesting Embelia subcoriacea Mez. (Myrsinaceae) and Petanovicia discolor n. sp. infesting Sapium discolor (Champ. ex Benth.) Muell.-Arg. (Euphorbiaceae). A key to species of Phyllocoptruta from China is provided.